O brincar e a indústria cultural: é possível salvar a criança? - Burckardt, Eduarda Virginia (2017)
This study consists of restlessness and the desire to know the child and his relationships with the toy and play. In order to understand the affinity that is established between the artifacts produced by the Cultural Industry, which we will call industrialized toys and play, more precisely the “play and self-move” of the child. To do so, to think the child in his world of play and its relation with the industrialized toy, it is necessary to confront them with the social and cultural processes that portray contemporaneity. This research is characterized as a Theoretical Research, which intends to seek more elements to discuss this theme, seeking to dialogue with different authors in order to increase the studies on the subject. Thus, the work builds a dialogue placing the child and his play, debating some fundamentals with more recent criticism about the involvement increasingly intense and precocious child with the adult´s world. Then we will deepen the look at the Cultural Industry and its reflections on the life of the child, their forms of invasion in the universe of children and highlighting the electronic toys and the technological demands and their possible crossings in the development of the child. Without pretensions to present a solution, but in the intention of launching an alert, for teachers and adults in general, we focus on the understanding of play and self- move as a possibility to think the child in its essence, valuing their perceptions of living the now, in its potentialities and possibilities that are discovered through the curiosity of children, and thus, establishing a dialogue with the world. In this way, this writing proposes to debate the intentions of the industrialized toy and the play in its essence, trying to problematize the importance of playing and self-move, proposing an alert to the institutions of early childhood education.